The risk factors of progestational anxiety, depression, and sleep disturbance in women with recurrent pregnancy loss: A cross-sectional study in China - Wang, Ting-ting; Liu, Yi-lin; Hou, Yue; Li, Jia-po; Qiao, Chong (Frontiers in Psychology, 2023)
Background The risk factors of progestational anxiety, depression, and sleep disturbance in women with a history of recurrent pregnancy loss (RPL) remain controversial, additional study is needed to investigate the incidence and risk factors of progestational anxiety, depression, and sleep quality in RPL women. Methods A cross-sectional study was conducted among 663 non-pregnant RPL women in Northeast China from October 2019 to July 2022. We assessed the state of anxiety, depression, and sleep quality before pregnancy using structured questionnaires, including sociodemographic characteristics, state-trait anxiety scale (STAI), center for epidemiological survey, depression scale (CES-D), Pittsburgh sleep quality index (PSQI), and symptom self-rating scale (SCL-90). Logistic regression was used to evaluate the association between sleep quality and anxiety, depression. Pearson’s correlation was used to evaluate the correlation between anxiety and depression. Multivariate logistic regression analysis was used to find the risk factors of depression symptoms. The receiver operating characteristic curve (ROC) was used to evaluate the predictive value of the model. Results The incidence of state anxiety, trait anxiety, depression, and sleep disturbance in RPL women were 60.3, 51.7, 33.9, and 31.2%, respectively. The level of anxiety and depression in RPL women varied at different stages of treatment. In a longitudinal study (25 pairs), we found the level of state anxiety and trait anxiety were significantly lower after the cause was identified. Sleep disturbance is positively correlated with anxiety and depression. Logistic regression showed that the number of miscarriages ≥4 (Odds ratio (OR) = 2.268, 95%CI 1.300–3.956), Low household family income (OR = 1.613, 95%CI 1.036–2.513/OR = 2.361, 95%CI 1.095–5.092), interval since last miscarriage <6 months (OR = 2.154, 95%CI 1.246–3.726) and sleep disturbance (OR = 5.523, 95%CI 3.542–8.614) were associated with the occurrence of depressive symptoms. At the same time, anxiety can be used as a predictor of depression. Conclusion Recurrent pregnancy loss women have a certain degree of anxiety, depression, and sleep disturbance. Education level, interval since the last miscarriage <6 months, and sleep disturbance are risk factors for anxiety and depression. A history of pregnancy loss after 14 weeks and no living birth are also closely related to anxiety. Therefore, it is necessary to pay close attention to the psychological state of RPL women and provide appropriate psychosocial support to reduce the occurrence of negative emotions.